Intersecting risks: A longitudinal analysis of climate exposure, social vulnerability, and mental health in the Texas Gulf Coast - Xu, Lulu; Adepoju, Omolola E.; Tipton, Mary E.; Rifai, Hanadi (Frontiers in Public Health, 2025)
This study investigates the evolving intersection of social vulnerability, climate exposure, and mental health distress in Harris County, Texas, from 2014 to 2022, with projections through 2030. Using census tract-level data and integrating indicators from the CDC Social Vulnerability Index, climate exposure metrics, and mental health outcomes, we developed predictive models to forecast future trends. Results indicate a significant rise in overall social vulnerability—from a score of 8.16 in 2022 to 8.87 by 2030, driven by increasing poverty, extreme heat, flooding, and deteriorating mental health. Mental health distress is projected to escalate from 18.7.0% to 22.7% of the population, underscoring a growing public health burden. The study highlights the compounding risks faced by underserved communities and emphasizes the need for targeted planning, mental health workforce expansion, and adaptive infrastructure strategies. These findings offer critical insights for policymakers and public health officials aiming to mitigate future climate-related health disparities.